Ibāḍism East of Mesopotamia: Early Islamic Iran, Central Asia and India - Salimi, Abdulrahman al- (Dar al-Farabi : Klaus Schwarz Verlag, 2016)
Keywords: Ibadisme – Asie centrale

The research on Medieval Ibadism in Oman : historiographical tendencies and documentary resources - Salimi, Abdulrahman al- (2011)

Early Ibāḍī Creed in the 2nd/8th Century: A Study of Wā'il Bin Ayyūb's “Nasab Al Islam” (“the Lineage of Islam”) - Salimi, Abdulrahman al- (The Muslim World, 2015)
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/muwo.12088
Keywords: Foi – Traité – 8e siècle

The political organization of Oman from the Second Imamate period to the Yaʻrūba: rereading Omani internal sources - Salimi, Abdulrahman al- (2013)

Oman and Ibadism from a Religious Regional Perspective - Salimi, Abdulrahman al- (Istituto Lombardo - Accademia di Scienze e Lettere - Incontri di Studio, 2017)
Questo paper affronta il tema dell’identità Omanita e l’ideologico religioso Islamico Ibadita. Fra gli elementi principali che caratterizzano l’Oman, si possono considerare: 1. La sua particolare configurazione geografica. 2. La sua popolazione multi-culturale e multi-religiosa sin da epoche antichissime e precedent l’Islam stesso. 3. La dottrina Islamica Ibadita. Conseguentemente, in primo luogo l’Autore si sofferma sulle particolari connotazioni geografiche dell’Oman e suoi molteplici ‘paesaggi’, i quali hanno indubbiamnete avuto un profondo impatto sugli habitat umani e la loro organizzazione all’interno delle diverse nicchie ecologiche del Paese, risalendo a secoli se non a millenni or sono. Riguardo a quest’ultimo aspetto, una delle principali connotazioni è stata quella del tribalismo e le sue complementarietà all’interno di una cornice che, in Oman, è sempre stata caratterizzata da multi-culturalità e multi-religiosità. Quindi, con l’avvento dell’Islam, un nuovo fattore si è imposto sulla scena storica omanita: l’Ibadismo e le sue dinamiche. Dopo un breve schema storico e in ampia parte riferendosi al paper precedente, il discorso puntualizza i principî base dell’Ibadismo e della sua evoluzione nel tempo, il ruolo giocato in Oman nel corso dei secoli, il suo impatto sulla società locale e il modello politico-istituzionale che esso ha contribuito a forgiare e modellare. Si tratta di una eredità culturale tramandata nei secoli fino ad oggi. Infine, l’Autore dà un rapido ma chiaro affresco dell’Ibadismo e del suo ideologico religioso oggi, il rapporto fra questa ideologia religiosa e il concetto di Modernità tecnologica e sociale, Corano e principî guida religiosi di fronte alle diversità, la risposta Ibadita di fronte a un nuovo modello di società inter-religiosa e inter-etnica.

The Sirah to the People of Khwarazm - Salimi, Abdulrahman al- (Ibāḍism East of Mesopotamia: Early Islamic Iran, Central Asia and India, 2016)
Keywords: Ibadisme – Asie centrale

The Cosmology Argument in Early Ibadi Theology - Salimi, Abdulrahman al- (2010)

The Sirah to the People of Khurasan - Salimi, Abdulrahman al- (Ibāḍism East of Mesopotamia: Early Islamic Iran, Central Asia and India, 2016)
Keywords: Ibadisme – Asie centrale

Early Islamic law in Basra in the 2nd/8th century: Aqwal Qatada b. Diʻama al-Sadusi - Salimi, Abdulrahman al- (Brill, 2018)
Keywords: Fiqh

Ibadism and Oman - Salimi, Abdulrahman al- (2015)

An Exaggeration of Qur’an by the Baghdadi Mu‘tazilite: Studying Abu Tahir al-Turaythithi - Salimi, Abdulrahman al- (Manuscripta Orientalia, 2014)
The objective of this paper is to shed the light to the series of manuscripts of the treatise al-Mutashabih fi al-Qur’an ( Ambiguous [ayat] in the Qur’an ) by Abu Tahir al-Turaythithi, Mu'tazilte scholar of Baghdad. The problem discussed is the exaggeration of the Qur’an which was the point of sharp theological debates. We know comparatively well the Mu'tazilte works produced in Basra while the work by Abu Tahir al-Turaythithi reflects comprehensively the school of Baghdad. The journey of the treatise through the Muslim world as presented by its manuscripts started from Central Asia, they appeared in Yemen and Oman and finally in one of the European libraries.
Keywords: Coran – Commentaires

A comparison of modern religious education in Arabia: Oman and Yemen - Salimi, Abdulrahman al- (2011)
FMC 13 p.
Keywords: Enseignement – Oman

Early Ibāḍī Theological Arguments on Atoms and Accidents - Salimi, Abdulrahman al- (Arabic Sciences and Philosophy, 2013)
Le gros de la recherche orientaliste consacrée à la littérature théologique islamique a négligé les idées théologiques Ibāḍī à portée cosmologique, ce qui a conduit à une compréhension incomplète de la théologie islamique et à un manque considérable dans la recherche occidentale. L'omission de ce mouvement important de l'Islam est compréhensible étant donné que les textes Ibāḍī ne sont accessibles, publiés, diffusés et traduits que de façon très partielle. Cette étude vise donc à combler certaines de ces lacunes dans la recherche sur la première théologie islamique. Les objectifs de cet article sont de: 1) caractériser la littérature Ibāḍī classique portant sur la théorie atomiste de la substance et de l'accident; 2) examiner les textes d'auteurs Ibāḍī du iiie/ixe siècle dialoguant et discutant avec d'autres écoles théologiques islamiques, à savoir les Muʿtazilites pré-Bahshamiyya (Abū Hāshim al-Jubbāʾī, d. 321/933) et les Ashʿarites (Abū al-Ḥasan al-Ashʿarī, d. 324/936), en lien avec la théorie atomiste de la substance et de l'accident; 3) passer en revue le grand nombre d'opinions soutenues parmi les premiers théologiens Ibāḍī, et examiner les sources et les thèmes spécifiques susceptibles d'avoir influencé cette école de pensée diversifiée. Cet article cherche aussi à identifier des traits communs dans l'approche Ibāḍī durant la période de formation de la théologie islamique, et à explorer les voies grâce auxquelles ces premiers théologiens ont pu avoir accès à des thèmes cosmologiques antérieurs à l'Islam.

On the Significance of the Aqwal Qatada for Early Islamic Legal Thought - Salimi, Abdulrahman al- (2017)
The Aqw?l Qat?da (the Sayings/teachings of Qat?da) is a collection of writings on fiqh (jurisprudence) and ?ad?th (traditions) narrated by Qat?da b. Di'ama al-Sadusi (c.60-117/680-735) that has frequently attracted the interest of present-day scholars. In addition to these writings, the discovery of a number of previously unknown texts on Ib??? jurisprudence and early legal opinions in the Maghrib region by a non-Ib??? scholar from Ba?ra now raises important questions about early Ib??? history and the proper methods of recording information during Islam’s formative period during the first half of the 2nd /8th century. Although these texts have not yet been published, they are the subject of intense debate amongst modern scholars. Although the Aqw?l Qat?da was never incorporated into the legal literature of the Ib??iyyah in Oman, manuscripts of the Aqw?l Qat?da have repeatedly attracted particular interest among modern scholars as it raises questions concerning the early development of the Ib??? Ba?ran community. It is a unique document because it attests to the existence of a scholarly link between Sunn?s and Ib???s during the early development of Islamic law. The fact that the legal responses and traditions of Qat?da are part of an Ib??? collection, in which the traditions of J?bir bin Zayd (one of the founders of Ibadism) have been transmitted through ‘Amr b. Harim and ‘Amr b. D?n?r, proves that Ib??? lawyers of the first generations considered Qat?da to be a faithful upholder of J?bir's doctrine. This present study on the text is based on two recently discovered manuscripts. One of these is in the D?r al-Kutub al-Mi?riyyah in Cairo, while the other is in the al-B?r?niyyah Library (al-Khiz?nah al-B?r?niyyha) on the Tunisian island of Djerba. We shall look at both of them in detail. The texts display three important features, which will be the subject of analysis: 1) fiqh opinions commonly held during the early Islamic period in Ba?ra; 2) early approaches to the collection of Islamic religious traditions including ?ad?th of the Prophet and legal opinions of the early community 3) the development of Islamic jurisprudence during the first two centuries of the Islamic era.
Keywords: Fiqh

The Transformation of Religious Learning in Oman: Tradition and Modernity - Salimi, Abdulrahman al- (Journal of the Royal Asiatic Society, 2011)
The last fifty years mark a period of great change in the role of religious leadership and education in the Sultanate of Oman. The country moved from bifurcated leadership between an Imam and a Sultan to a single political authority. These decades also witnessed the modernisation of the state. These factors combined to reshape the place of religion and religious education in society. Whereas previously religious leaders had relative autonomy and more direct political influence, now they were brought under the auspices of the government with their focus circumscribed to religious matters. The structures and foci of religious education were then reshaped so that tradition provided a platform for progress and the more zealous ideologies emerging in the region could be held at bay. This has permitted Oman to modernise and engage with a global society in an amicable, non-sectarian, manner.
Keywords: Enseignement – Oman

Poetic Anthology of Ibāḍī Theology. Historical Readings of Ibn al-Naẓar’s al-Daʿāʾim and its Commentaries - Salimi, Abdulrahman al- (Der Islam, 2016)
Keywords: Poésie – Oman

The Collection of Ḥadīth in Early Islamic Iraq (2nd/8th Century): The Musnads Al-Rabī‘ b. Ḥabīb and Zayd ibn ‘Alī - Salimi, Abdulrahman al- (2018)
Keywords: Hadith – Exégèse

The New Silk Road and the Communication between the Middle East and China - Salimi, Abdulrahman al- (Krakowskie Studia Międzynarodowe, 2017)
Termin „Jedwabny Szlak” ma dwa znaczenia: dosłowne i metaforyczne. W czasach, kiedy termin ten został wprowadzony do obiegu, centrum handlowym ówczesnego globalnego świata był świat arabski. Później centrum to przesunęło się na zachód, w dużym stopniu ze względu na chaos i zaburzenia, które zaczęły wstrząsać Bliskim Wschodem. W kolejnym okresie handel światowy zaczął intensywnie rozwijać się na Dalekim Wschodzie, z którym ściśle powiązana jest Zatoka Arabska/ Perska oraz basen Morza Czerwonego. Dzisiaj gospodarcze znaczenie Jedwabnego Szlaku staje się ważniejsze niż kiedykolwiek. W artykule analizowane są kulturowe aspekty idei Jedwabnego Szlaku oraz formy, w jakich ta idea zaczyna się wyrażać.

Trends in Religious Reform on the Arabian Peninsula - Salimi, Abdulrahman al- (Hemispheres, 2012)
This article comparatively assesses the relationship of Arabian Peninsula governments to modern Islamic reform movements after the formation of nation-states by the British Government in post-Ottoman Arabia. Over the last half century the region of the Arabian Peninsula has experienced an Islamic awakening that has played an integral role in the process of modernization in Arabian states. There are three aims of this study: 1) to examine the influence of the traditional Islamic schools of theology on re-shaping the identities of Arabian states. 2) to explore the degree to which the governments of the nation states and the prior political establishments informed the contemporary vision of religious reform 3) to consider the impact that the recent wealth of Arabian States, especially the wealth of the GCC countries, has had on the creation of the modern Islamic revival since the discovery of oil. [PUBLICATION ABSTRACT]

The Influence of Ibāḍī siyar on the Orientalists’ Understanding of the Formation of Islam - Salimi, Abdulrahman al- (2017)
Keywords: Orientalisme – Ibadisme

The Influence of Ibadi Siyar Manuscripts on the Orientalists'' Understanding of the History of Early Islamic Theology - Salimi, Abdulrahman al- (Manuscripta Orientalia, 2017)
The article is devoted to the achievements and approaches of specialists, mostly American, British, German, French and Italian in the analysis of Ibadi siyar and the new perspectives of the research connected with the analysis of the MSS material. The general tendency in the field now is to follow the footsteps of Van Ess, Madelung and Cook, and rather than developing new theories and hypotheses, to seek out and identify well documented texts that will offer a reliable picture of Islamic thought before the 3rd/9th century. To provide a clearer general context, the texts could also be rearranged in historical order and grouped on the basis of the ideas they present. Most works produced by the different Ibadi groups during the early period are not representative of particular literary genre. However, we do not have precise data on the Islamic material on ‘ilm al-kalam that has been discovered so far from the period up to the end of the 3rd/9th century. Because of the importance attached to siyar by Ibadi ‘ulama’ during the 10th/16th and 11th/17th centuries Ibabi schools began to seek out their roots and collect early manuscripts and works of literature on the Ibadi legacy... The article is devoted to the achievements and approaches of specialists, mostly American, British, German, French and Italian in the analysis of Ibadi siyar and the new perspectives of the research connected with the analysis of the MSS material. The general tendency in the field now is to follow the footsteps of Van Ess, Madelung and Cook, and rather than developing new theories and hypotheses, to seek out and identify well documented texts that will offer a reliable picture of Islamic thought before the 3rd/9th century. To provide a clearer general context, the texts could also be rearranged in historical order and grouped on the basis of the ideas they present. Most works produced by the different Ibadi groups during the early period are not representative of particular literary genre. However, we do not have precise data on the Islamic material on ‘ilm al-kalam that has been discovered so far from the period up to the end of the 3rd/9th century. Because of the importance attached to siyar by Ibadi ‘ulama’ during the 10th/16th and 11th/17th centuries Ibabi schools began to seek out their roots and collect early manuscripts and works of literature on the Ibadi legacy. The latter were copied and preserved per se without diluting them or considering them in the context of the other Islamic schools. That is why the Ibadi school was able to remain united and steadfast in the face of the contemporary modernization movements which continue to this day. Most of the compilations of the texts that are currently in our possession comprise not more than ten volumes in all. Scholars and copyists have rearranged each of these manuscripts, so that each copy has a different number and sequence of siyar texts. The existing text formats raise the important question of whether Ibabi siyar are actually a literary genre. Until now nobody has really studied siyar in such a way that their specific genre characteristics have been defined in detail.

Regulating the Sea: A 9th Century Ibadi Manuscript on Maritime Law - Salimi, Abdulrahman al- (2018)

Reconstructing Ibāḍī Theology in North Africa: the influence of ʿAbdallāh ibn Yazīd al-Fazārī - Salimi, Abdulrahman al- (2019)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

Identifying the (Ibadi/Omani) Siyar - Salimi, Abdulrahman al- (Journal of Semitic Studies, 2010)
Keywords: Prosopographie – Oman

The Religious Policies in Oman: Renewal in the Modern State - Salimi, Abdulrahman al- (Oman, Ibadism and modernity, 2018)

Ibadi Studies and Orientalism - Salimi, Abdulrahman al- (On Ibadism, 2014)
Keywords: Orientalisme – Ibadisme

Oman: a maritime history - Salimi, Abdulrahman al-; Staples, Eric (Georg Olms Verlag, 2017)
Keywords: Navigation – Oman

The Political Organization of Oman from the Second Imamate Period to the Yaʻrūba: Rereading Omani Internal Sources - Salimi, Abdulrahman al- (L’ibadisme dans les sociétés de l’Islam médiéval, 2018)

A maritime lexicon: Arabic nautical terminology in the Indian ocean: English-Arabic edition - Salimi, Abdulrahman al-; Staples, Eric (Georg Olms Verlag, 2019)
Keywords: Navigation – Oman

Ibāḍism and the Creation of the Qur’ān - Salimi, Abdulrahman al- (Ibadi theology: rereading sources and scholarly works, 2015)

Reflections of a Muslim-Portuguese maritime world in a sixteenth-century Portuguese source - Salimi, Abdulrahman al-; Staples, Eric (Proceedings of the Seminar for Arabian Studies, 2015)
This paper discusses a record of expenses of an early sixteenth-century Portuguese vessel, the Santa Maria do Monte, during its voyage from Goa to Hormuz and back in 1520-1521, stopping in the Omani ports of Qalhāt, Ṭīwī, Qurayyāt, Muscat (Masqat), and Khawr Fakkān along the way. The route sailed during this voyage is examined in light of regional navigational practices, and the composition of the crew is discussed, emphasizing the significant non-Portuguese population on board. The nature of the ship and the specific costs of maintaining this vessel during the voyage are also addressed. Collectively, the cultural intersections involved with the navigation, the crew, and the maintenance regime of this vessel provide specific examples of maritime relationships in the region. In terms of its broader significance, such evidence of a high concentration of regional actors in a Portuguese instrument of maritime power alludes to a more complex and interdependent relationship between the Portuguese and the Arabian Sea maritime spheres. It also highlights a specific segment of the vibrant maritime Indian Ocean mosaic that the Portuguese were compelled to navigate during their imperial endeavours.
Keywords: Relations – Oman – Portugal

The Ibadis in the region of the Indian Ocean. Sect. 1: East Africa - Gaube, Heinz (Georg Olms Verlag, 2013)
Keywords: Ibadisme – Afrique de l'Est

The ports of Oman - Salimi, Abdulrahman al-; Staples, Eric (Georg Olms Verlag, 2017)

Ibāḍī texts from the 2nd/8th century - Salimi, Abdulrahman al-; Madelung, Wilferd (Brill, 2018)
In 'Ibāḍī Texts from the 2nd/8th Century' Abdulrahman Al-Salimi and Wilferd Madelung present an edition of fourteen 'Ibāḍī' religious texts and explain their contents and extraordinary source value for the early history of Islam. The 'Ibāḍīs' constitutes the moderate wing of the Kharijite opposition movement to the Umayyad and ʿAbbasid caliphates. The texts edited are mostly polemical letters to opponents or exhortatory to followers by ʿAbd Allah b. Ibāḍ, Abu l-ʿUbayda Muslim b. Abi Karima and other Ibāḍī leaders in Basra, Oman and Hadramawt. An epistle detailing the offences of the caliph ʿUthman is by the early Kufan historiographer al-Haytham b. ʿAdi. By their early date and independence of the mainstream historical tradition these txts offer the modern historian of Islam an invaluable complement to the well-known literary sources
Keywords: Sources – Ibadisme

Illuminated Qurans from Oman - Gaube, Heinz; Salimi, Abdulrahman al- (Georg Olms Verlag, 2016)
This book is a first attempt to present Omani Quranic manuscripts and their illuminations to a wider public and to discuss their originality in the wider context of Quranic manuscripts, Islamic art as a whole and beyond that in the wider context of Oriental art in general. This book focuses on the most prominent components of Quran illuminations, the frontispieces. The organization of the material starts with the most unpretentiously designed, plain frontispieces without frames and without horizontally subdivided pages and ends with one-page or double-page frontispieces with illuminations in two well-defined different styles which can be subdivided into several under groups. The first of these styles is named "Omani" and the second "Persian influenced" The first style is characterized by primarily geometric ornaments whereas vegetal forms and sophisticated designs distinguish the second. The origin of the second style can be easily traced back to Iran, most probably Southern Iran and there to the school of Shiraz. This style is closely related to the art of India Quran illuminations which doubtlessly had influenced Omani Quran illuminations too. The question of the origins of the fascinating first style, which has no equals in the Islamic world, can be answered in different ways and will be discussed in a separate subchapter
Keywords: Manuscrits – Oman

Portugal in the sea of Oman: religion and politics: research on documents - Salimi, Abdulrahman al-; Jansen, Michael (von Zabern, 2012)
Keywords: Relations – Oman – Portugal

Biographical Dictionaries in Oman - Salimi, Abdulrahman al- (Today's perspectives on Ibadi history, 2017)
Keywords: Biographies – Oman

Muslims, Scholars, Soldiers: The Origin and Elaboration of the Ibadi Imamate Traditions * By ADAM GAISER. - Salimi, Abdulrahman al- (Journal of Islamic Studies, 2013)
Keywords: Recension

سلسلة الدراسات الإباضية والعمانية المجلد الثاني: كتاب عمان وما وراء البحار - بنت ناصر, فاطمة (شباب التفاهم, 2018)
Keywords: Recension

The Essentials of Ibāḍī Islam, by Valerie J. Hoffman - Salimi, Abdulrahman al- (Ilahiyat studies, 2013)
Keywords: Recension

The Sirah of Imam Râshid b. Sa'id to the People of Mansürah - اليحمدي, راشد بن سعيد (Ibāḍism East of Mesopotamia: Early Islamic Iran, Central Asia and India, 2016)
Keywords: Ibadisme – Asie centrale

The Omani Renaissance: Renewal of Fiqh and Religious Reform - Sayyid, Ridwan al- (Oman, Ibadism and modernity, 2018)
Keywords: Fiqh

The southern Batinah ports - Jawhari, Nasser Said al- (The ports of Oman, 2017)

The Iftāʾ Office of Oman: Its Objectives and Policy - Sulaimi, Abdullah Ahmed al- (Oman, Ibadism and modernity, 2018)

The Development in the Ibāḍī Theology during the 18th and 19th Centuries - Busaidi, Saleh Ahmed al- (Oman, Ibadism and modernity, 2018)

Oman and Islamic maritime networks (632-1507 CE) - Staples, Eric (Oman: a maritime history, 2017)
Keywords: Navigation – Oman

Jumuiya ya Kiislamu ya Istiqaama Tanzania and Modern Ibāḍism in East Africa, 1985–2016 - Mathews, Nathaniel (Oman, Ibadism and modernity, 2018)
Keywords: Zanzibar

Muscat and Mutrah - Gaube, Heinz (The ports of Oman, 2017)

Le grand réformateur Shaykh Bayyūḍ tel que je l’ai connu Ibrāhīm b. ʿUmar, 1313–1401/1899–1981: un témoignage - Jaabiri, Farhat (Oman, Ibadism and modernity, 2018)
فرحات بن علي الجعبيري
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

The port of Gwadar and its relationship with Oman - Nicolini, Beatrice (The ports of Oman, 2017)

The development of boatbuilding technologies and typologies - Vosmer, Tom (Oman: a maritime history, 2017)
Keywords: Archéologie – Oman

Al-Salimi, Abdulrahman / Madelung, Wilferd: Early Ibāḍī Literature. 2011. - Rebstock, Ulrich (Orientalistische Literaturzeitung, 2017)
Keywords: Recension

Oman’s maritime activities throughout the Indian Ocean 1650-1856 CE - Nicolini, Beatrice (Oman: a maritime history, 2017)
Keywords: Navigation – Oman

Julfar and the ports of northern Oman - Power, Timothy (The ports of Oman, 2017)

Review of Early Ibāḍī Literature. Abu l-Mundhir Bashīr b. Muḥammad b. Maḥbūb. Kitāb al-Raṣf fi l-Tawḥīd, Kitāb al-Muḥāraba and Sīra. (Abhandlungen für die Kunde des Morgenlandes, 75) - Prevost, Virginie (Wiener Zeitschrift für die Kunde des Morgenlandes, 2012)
Keywords: Recension

Ibāḍī Policy on Education and Learning in the Premodern Period - Kondo, Yohei (Oman, Ibadism and modernity, 2018)
Keywords: Enseignement – Oman

The Critique of Ḥadīth in Early Ibāḍī Literature - Salimi, Abdulrahman al- (Local and global Ibadi identities, 2019)

Religion and Politics in Ibāḍism: A Historical Survey - Madelung, Wilferd (Oman, Ibadism and modernity, 2018)

Navigation in Islamic sources - Staples, Eric (Oman: a maritime history, 2017)
Keywords: Navigation – Oman

Ports in the Indian Ocean - Pearson, Michael (The ports of Oman, 2017)

Conclusion: the ports of Oman today - Staples, Eric (The ports of Oman, 2017)

East Africa and Oman, c. 600-1856 CE - Horton, Mark (The ports of Oman, 2017)
Keywords: Relations – Oman – Afrique de l'Est

The Notion of Jesus’ Return in the Views of Two Ibāḍī Scholars: Muḥammad Aṭfayyish and Aḥmad al-Khalīlī - Albayrak, Ismail (Oman, Ibadism and modernity, 2018)
Keywords: Atfiyyash; Muhammad b. Yusuf (1821-1914); Coran – Commentaires – 19e siècle; Coran – Commentaires – 20e siècle

Hinterland trade and maritime networks in Oman from Iron Age to Late Antiquity (1000 BCE-630 CE) - Reddy, Anjana (Oman: a maritime history, 2017)
Keywords: Archéologie – Oman

Abdulrahman al-Salimi / Heinz Gaube (eds.): A New Collection Dedicated to Ibadism and Oman: A Review of the First Four Publications (2013–4) - Aillet, Cyrille (Der Islam, 2015)
Keywords: Recension

Early Ibāḍī Theology : Six kalām texts by ʿAbd Allāh b. Yazīd al-Fazārī, written by Abdulrahman al-Salimi and Wilferd Madelung - Aillet, Cyrille (Arabica, 2017)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Recension

Was There an Arab Intellectual Revival (Nahḍa) in the 17th and 18th Centuries? A Review Essay - Lange, Christian (Oman, Ibadism and modernity, 2018)

Redefining Ibāḍī Identity through Religious Discourse in the Time of the Nahḍa - Ziaka, Angeliki (Oman, Ibadism and modernity, 2018)
Keywords: Réformisme

Omani State Policies Concerning Buddhist Expatriates: Their Effects and Significance for the Sri Lankan Theravāda Community in Muscat - Wrona, Alexander (Oman, Ibadism and modernity, 2018)

Omani-Portuguese maritime activities (1500-1650 CE) - Floor, Willem (Oman: a maritime history, 2017)
Keywords: Relations – Oman – Portugal

Qalhat and Sur - Vosmer, Tom (The ports of Oman, 2017)
Keywords: Archéologie – Oman

Generic Islam? Official Religious Discourse in the Sultanate of Oman - Broucek, James (Oman, Ibadism and modernity, 2018)

Ijtihād and the Ibāḍī Reform Movement in North Africa: Shaykh Muḥammad Aṭfayyish’s ‘Re’-Interpretation of Kitāb al-Nīl - Francesca, Ersilia (Oman, Ibadism and modernity, 2018)
Keywords: Atfiyyash; Muhammad b. Yusuf (1821-1914); Réformisme – Mzab

Maritime trade in the Bronze Age - Vosmer, Tom (Oman: a maritime history, 2017)
Keywords: Archéologie – Oman

The ancient port of Sumhuran - Avanzini, Alessandra (The ports of Oman, 2017)
Keywords: Archéologie – Oman

Islamic Modernisms: An Ibāḍī-Shīʿite Perspective - Modaressi, Hossein (Oman, Ibadism and modernity, 2018)
Keywords: Réformisme

Review of Early Ibāḍī Theology. Six kalām texts by ʿAbd Allāh b. Yazīd al-Fazārī. (Islamic History and Civilization 106) - Thiele, Jan (Wiener Zeitschrift für die Kunde des Morgenlandes, 2016)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Recension

Islamic art in Oman - Salimi, Abdulrahman al-; Gaube, Heinz; Korn, Lorenz (Mazoon printing, publishing & advertising, 2014)
Keywords: Arts – Oman

Religious Tolerance in Oman and Ibāḍī Islam - Propst, Amanda (Oman, Ibadism and modernity, 2018)
Keywords: Tolérance religieuse – Oman

Sohar: forelands, Umland and Hinterland in the history of an Omani entrepôt - Averbuch, Brian (The ports of Oman, 2017)
Keywords: Navigation – Oman

Religion and Politics in Contemporary Omani Ibāḍism - Francesca, Ersilia (Oman, Ibadism and modernity, 2018)

Abdulrahman Al-Salimi and Wilferd Madelung (eds): Ibāḍī Texts from the 2nd/8th Century. (Islamic History and Civilization. Studies and Texts 133.) vi, 392 pp. Leiden: Brill. 2018. €110. ISBN 978 90 04 33064 1. - Gaiser, Adam R. (Bulletin of the School of Oriental and African Studies, 2018)
Keywords: Recension

Hormuz: Bandar and Mulk (port and dominion): eleventh to early sixteenth century CE. When Hormuz was the hinge of a new land and maritime system, and Oman was its pivot: the Hormuz - Oman - Kij mercantile dominion - Piacentini Fiorani, Valeria (The ports of Oman, 2017)

The Individual Reaction to Western Modernization - Ghazal, Amal N. (Oman, Ibadism and modernity, 2018)
Keywords: Réformisme

Ibāḍīs in the Cultural Memory of Modern Ḥaḍramawt - Rodionov, Mikhail A. (Oman, Ibadism and modernity, 2018)

Maritime history, world history, global history: some thoughts on past, present and future - Alpers, Edward A. (Oman: a maritime history, 2017)
Keywords: Navigation – Oman

The South East European View - Ziaka, Angeliki (Oman and overseas, 2013)

AL-SALIMI, A., and W. MADELUNG (eds.) — Early Ibadi Literature. Abu l-Mundhir Bashir b. Muhammad b. Mahbub, Kitab al-Rasf fi l-Tawhid, Kitab al-Muharaba and Sira - Custers, Martin H. (Bibliotheca Orientalis, 2012)
Keywords: Recension

Ibāḍism and State Formation in Oman - Wilkinson, John Craven (Oman, Ibadism and modernity, 2018)

AL SALIMI, A., and E. STAPLES (eds.) – Oman. A Maritime History - Custers, Martin H. (Bibliotheca Orientalis, 2018)
Keywords: Recension

The Heritage of Ibāḍism in the Medieval History of Ḥaḍramawt in the Context of the Ideological Struggle between the Irshādites and the ʿAlawites - Frantsouzoff, Serge A. (Oman, Ibadism and modernity, 2018)

From Colonial Documentation to Citizenship Boundaries: Marriage Policy across Two Nahḍas - Limbert, Mandana E. (Oman, Ibadism and modernity, 2018)

Early Islamic Theological Influence in Jurisprudence. An Ibāḍī Perspective - Salimi, Abdulrahman al- (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Fiqh – Ibadisme

AL SALIMI, A., and E. STAPLES (eds.) – The Ports of Oman - Custers, Martin H. (Bibliotheca Orientalis, 2018)
Keywords: Recension

Ibāḍism and the Tradition of Tolerance in Oman - Sheline, Annelle R. (Oman, Ibadism and modernity, 2018)
Keywords: Tolérance religieuse – Oman

Ibāḍī-Omani Creeds and the Construction of Omani Religious Discourse - Hoffman, Valerie J. (Oman, Ibadism and modernity, 2018)

Oman and Ibadism in Modern French Historiography: Assessing a Semi-Failure - Dridi, Moez (Oman and overseas, 2013)

Book review: Oman and Overseas éd. Michaela Hoffmann-Ruf et Abdulrahman al-Salimi, written by Oman and Overseas - Prevost, Virginie (Arabica, 2015)
"Book review: Oman and Overseas éd. Michaela Hoffmann-Ruf et Abdulrahman al-Salimi, written by Oman and Overseas" published on 04 Mar 2015 by Brill.
Keywords: Recension

The Formation of Oman’s Maritime Power under the Yaariba and Sayyid Said - Staples, Eric (Oman and overseas, 2013)

Oman: The Russian View since the 15th Century - Rezvan, Efim (Oman and overseas, 2013)
Keywords: Récits de voyage – Oman

A Historic Perspective on the Nahḍa - Wilkinson, John Craven (Oman, Ibadism and modernity, 2018)
Keywords: Réformisme – Oman

Ibadis in East Africa: Archaeological and Historical Evidence - Horton, Mark (Oman and overseas, 2013)
Keywords: Archéologie – Zanzibar

Umani Ports in Chinese Sources - Kauz, Ralph (Oman and overseas, 2013)

Early Ibāḍī Literature: Abu l-Mundhir Bashīr b. Muḥammad b. Maḥbūb Kitāb al-Raṣf fi l-Tawḥīd, Kitāb al-Muḥāraba and Sīra, by Abdulrahman al-Salimi and Wilferd Madelung (eds.) - Gaiser, Adam R. (Ilahiyat Studies, 2010)
Keywords: Recension

Religious Aspects in the Poetry of Abū Muslim al-Bahlānī - Michalak-Pikulska, Barbara (Oman, Ibadism and modernity, 2018)
Keywords: Littérature – Oman

A Political Culture and Foreign Policy Shaped by a Moderate Religious View: The Case of the Sultanate of Oman - Rabi, Uzi (Oman and overseas, 2013)
Keywords: Vie politique – Oman – 1970-2020

The Roots of Religious Tolerance in the Omani-Ibāḍī Tradition - Gaiser, Adam R. (Oman, Ibadism and modernity, 2018)
Keywords: Tolérance religieuse – Oman

Mosaic Oman: Views from India - Dietl, Gulshan (Oman and overseas, 2013)

From Slumber to Assertion: Maritime Expansion of the Ibadis of Oman and the Responses of Estado da India,1622–1720 - Malekandathil, Pius (Oman and overseas, 2013)

MADELUNG, W., and A. AL-SALIMI (eds.) – Ibāḍī Texts from the 2nd/8th Century. (M.H. Custers) - Custers, Martin H. (Bibliotheca Orientalis, 2019)
Keywords: Recension

Omani Seafaring and Omani Boat - Vosmer, Tom (Oman and overseas, 2013)
Keywords: Archéologie – Oman

The British Historical View of Oman and Ibadism - Worrall, James (Oman and overseas, 2013)

Ibāḍīs in Zanzibar and the Nahḍa - Hoffman, Valerie J. (Oman, Ibadism and modernity, 2018)
Keywords: Zanzibar

Abdulrahman Al-Salimi and Wilferd Madelung: Early Ibāḍī Theology: Six kalām Texts by ‘Abd Allāh B. Yazīd Al-Fazārī. (islamic History and Civilization.) Cvi, 241 Pp. Leiden: Brill, 2014. €99. Isbn 978 90 04 27025 1. - Gaiser, Adam R. (Bulletin of the School of Oriental and African Studies, 2015)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Recension

The Portuguese in East Africa and the Omani Reconquest of East Africa - Newitt, Malyn (Oman and overseas, 2013)
Keywords: Relations – Oman – Portugal

The Tragedy of the Arab World - Ech-Cheikh, Mohammed (Oman, Ibadism and modernity, 2018)

Oman through Jewish Travellers’ Eyes - Schreiner, Stefan (Oman and overseas, 2013)
Keywords: Judaïsme – Oman; Récits de voyage – Oman

الإباضية في منطقة المحيط الهندي.. القسم الأول - شرق أفريقيا - بنت ناصر, فاطمة (شباب التفاهم, 2018)
Keywords: Recension

Religion and Political Structure: The Berber-Ibāḍī Perspective in North Africa between Diversity and Pluralism - Di Tolla, Anna Maria (Oman, Ibadism and modernity, 2018)
Keywords: Berbérisme – Afrique du Nord

The Seminar für Orientalische Sprachen (SOS) at Berlin: Aspects of the Relationship between Oman and Germany in the Late 19th and Early 20th Century - Hoffmann-Ruf, Michaela (Oman and overseas, 2013)
Keywords: Relations – Oman – Allemagne

HOFFMANN-RUF, M., und A. AL SALIMI (Hrsg.) – Oman and Overseas. proceedings of the Inter- national Conference ‘The Ibadism of Oman - Its Overseas Development and its perception Over- seas’ held at Tübingen University, 16th-19th of May 2011. - Custers, Martin H. (Bibliotheca Orientalis, 2014)
Keywords: Recension

Wood, Horses and Friendship. The Arabic Letters from Muscat to the Dutch in Kochi (1779) and Batavia (1798–1806) - Witkam, Jan Just (Oman and overseas, 2013)

Late pre-Islamic Oman: The Inner Evidence – The Outside View - Yule, Paul A. (Oman and overseas, 2013)
Keywords: Archéologie – Oman

The Main Languages of East Africa and their Literatures - Bakari, Mohammed Ali (Oman and overseas, 2013)
Keywords: Littérature – Zanzibar

Oman’s maritime history since 1856 CE - Allen, Jr, Calvin H. (Oman: a maritime history, 2017)
Keywords: Navigation – Oman

A Historical Survey of US-Omani Relations from 1790 to the Present - Leonard, Douglas R. (Oman and overseas, 2013)
Keywords: Relations – Oman – Etats-Unis

Omani Trade and Cultural Relations with East Asian Countries - Ziaee, Ali Akbar (Oman and overseas, 2013)
Keywords: Commerce – Oman

African Perspectives - Kusimba, Chapurukha M. (Oman and overseas, 2013)

The Origins of Omani Identity - Wilkinson, John Craven (Oman and overseas, 2013)

The Growth of the Relationships between Oman, the Gulf and the Western Waters of the Indian Ocean. Oman: The Corner-Stone of a Maritime System - Piacentini Fiorani, Valeria (Oman and overseas, 2013)

Family in the Maghrib: The Case of Mzabi Society in the Nahḍa Period - Di Tolla, Anna Maria (Oman, Ibadism and modernity, 2018)

Ibāḍī Jurisprudence in Modern Context (International Perspectives) - Abou-el-Wafa, Ahmed (Oman, Ibadism and modernity, 2018)
Keywords: Fiqh; Fiqh – Ibadisme

Omani Seafaring Identity before the Early 1600s: Ethnic and Linguistic Diversity - Agius, Dionisius A. (Oman and overseas, 2013)
Keywords: Navigation – Oman

Ibāḍī Texts from the 2nd/8th Century - Love Jr, Paul M. (Al-Masāq, 2019)
Keywords: Recension

Danish and Norwegian Travel Accounts of Oman, 1765–1995: Changing Views across Sea and Land - Bang, Anne K. (Oman and overseas, 2013)
Keywords: Récits de voyage – Oman

Oman: The Arab Views - Ghazal, Amal N. (Oman and overseas, 2013)

The Christian and Hindu Communities in Oman (after 1970) - Howitz, Christopher J. R. (Oman, Ibadism and modernity, 2018)

Zanzibar: The Sultanate and the Ottoman State in Africa - Gol, Mohammed Z. (Oman and overseas, 2013)

Thamīnī, ʿAbd al-ʿAzīz al- - Calassanti Motylinski, Adolphe de; Lewicki, Tadeusz; Salimi, Abdulrahman al- (Encyclopaedia of Islam, 2010)
Keywords: Biographies – Mzab – 19e siècle

The Swahili Coast: Africa’s Window on the Indian Ocean - Sheriff, Abdul Mohamed Hussein (Oman and overseas, 2013)

Historical Coincidences between Oman and Brazil: Portuguese Invaders, African Slaves and the Majlis al-Jinn - Pacheco, Leila M. S. (Oman and overseas, 2013)
Keywords: Esclavage – Oman

Northern Indian Ocean Islamic seaports and the interior of the Arabian Peninusula - Zarins, Juris; Newton, Lynne (The ports of Oman, 2017)

Oman and Omanis in Portuguese Sources in the Early Modern Period (ca. 1500-1750) - Cunha, João Teles e (Oman and overseas, 2013)
Keywords: Relations – Oman – Portugal

Early Ibāḍī Literature: Abu l-Mundhir Bashīr b. Muḥammad b. Maḥbūb Kitāb al-Raṣf fi l-Tawḥīd, Kitāb al-Muḥāraba and Sīra - Ibn Maḥbūb, Bashīr ibn Muḥammad (Harrassowitz Verlag, 2011)
Kitāb al-raṣf fī al-tawḥīd wa-aḥkām al-Qurʼān wa-al-asmāʼ wa-al-aḥkām wa-al-Sunnah wa-al-Imāmah wa-asmāʼ al-dār wa-aḥkāmuhā wa-ḥudūth al-ʻālam – Kitāb al-muḥārabah – Sīrat al-shaykh Bashīr ibn Muḥammad ibn Maḥbūb fī al-ḥadath al-wāqiʻ bi-ʻUmān
Keywords: Foi – Traité

Early Ibāḍī theology: six kalām texts - Fazārī, ʿAbd Allāh ibn Yazīd (Brill, 2014)
Kitab al-qadar (Book of predetermination) Kitab fi l-radd ʻala Ibn ʻUmayr (Book on refutation of Ibn ʻumayr) Kitab al-radd ʻala al-mujassima (Book of refutation of the Corporalists) Kitab al-futya (Book of legal opinion) Kitab al-tawḥid fi maʻrifat Allah (Book of monotheism in the recognition of God) Kitab fi man rajaʻa ʻan ʻilmih wa-faraqa al-Nabi wa-huwa ʻala dinih – (Book about whoever reneges on his knowledge and departs from the Prophet while remaining in his religion
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

His Majesty Sultan Qaboos as a Paradigm of Peace: Images in Foreign Writings and Media - Hajri, Hilal al-; Panagiotou, Nikolas S. (Oman, Ibadism and modernity, 2018)
Keywords: Vie politique – Oman – 1970-2020

The Development of Ibāḍī Jurisprudence Writing in Oman: al-Imām al-Sālimī as a Model - Shueili, Sulaiman bin Ali bin Amir al- (Oman, Ibadism and modernity, 2018)

Religious Education in General and Higher Education in Oman: Reality, Rationale, and Institutional Practices - Ḥusaynī, Sulaymān ibn Sālim ibn Nāṣir (Oman, Ibadism and modernity, 2018)

Islamic period Maritime trade and travel along the southern Arabian coasts of the Indian Ocean: the case of Socotra, the Hallaniyat, Masirah and Mabut islands - Zarins, Juris; Newton, Lynne S. (The ports of Oman, 2017)

The Sultanate of Oman: Geography, Religion and Culture - Salimi, Abdulrahman al-; Abbaspour, Mitra; Kelemen, Peter; Limbert, Mandana E. (2015)
The Cooper Union for the Advancement of Science and Art

Tolerance, Sincerity and Hospitality, as Experienced by European and American Travelers Visiting Oman in the 19th and 20th Centuries - Ḥusaynī, Sulaymān ibn Sālim ibn Nāṣir (Oman, Ibadism and modernity, 2018)
Keywords: Tolérance religieuse – Oman